Birth Certificate Data Archive System with Web-Based Waterfall Method at the Population and Civil Registration Service of Central Aceh - Ira Zulfa; Salmandi Salmandi; Faradilla Faradilla (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
The birth certificate archive management system at the Central Aceh Population and Civil Registration Office still uses manual methods, which causes data search and storage to be less efficient. Therefore, this study aims to design and develop a web-based birth certificate data archive information system with the Waterfall method so that the management of data is more effective, secure, and organized. The development method used is Waterfall, which consists of the stages of analysis, design, implementation, testing, and maintenance. This system was built using the PHP programming language with the Laravel framework, and using MySQL as a database. The results of implementation shows that this system is able to manage archives digitally, facilitate data search, and reduce the risk of loss or damage to physical documents. System testing is carried out using the Black Box Testing method, which shows that all main features of the system function in accordance with the designed specifications. Evaluations from users of the system also show that the system is easy to use and increases efficiency in managing birth certificate archives. With this system, it is expected that the population administration process at the Population and Civil Registration Office of Central Aceh can run faster and more accurately, and provide better services to the community.